AICCRA Zambia Progress on the 2024 Work Plan - Jacobs-Mata, Inga; Kakwasha, Keagan; Chinemberi, Evans (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This presentation outlines the AICCRA Zambia 2024 work plan with local partners.